Intergovernmental Finance in Hungary : A Decade of Experience 1990-2000 - Kopányi, Mihály (Washington, DC: World Bank, 2013)
This book illustrates the decade-long transformation of the Hungarian sub-national system with a focus on sub-national finance. It shows the rocky path of transition from central command to decentralized local self-governments. Hungary has decentralized and refurbished the state administration, reestablished full autonomy of local governments, and tightened budget constraints. The public and private sectors are bound to each other in public utility supply, and civic organizations are also undertaking a growing role in providing social services. The book summarizes what worked well and what did not, and why, and then shows the challenges the country faces on entering the European Union. Although the process is still incomplete and the results are not perfect, Hungary's transition and its innovative and adaptive local governments have proven the merits of fiscal decentralization. The book builds upon dozens of policy analyses prepared by local and international specialists. The studies have provided a broad range of evidence of a steady learning process, against the background of a deep economic recession, and an inevitable fiscal squeeze in the midst of the 1990s. Hungary not only was a pioneer reformer, but it moved far ahead of other transition economies in devolving central functions to the local level, and, in developing an adequate legal and regulatory framework for a deeply decentralized system. The book consists of two parts. The first is a comprehensive overview of developments in the 1990s with a list of policy proposals in view of Hungary's advanced stage of transition. The second part consists of 28 case studies in three sections. The first addresses issues of enhancement of the overall intergovernmental system, while the second sets out experiences in building local government capacities in strategic management and finance. The last section addresses requirements for building a competitive framework for financing sub-national governments.